PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN PENGGUNA DOMPET DIGITAL LINKAJA SYARIAH (PADA MAHASISWA PRODI PERBANKAN SYARIAH PRODI PERBANKAN SYARIAH ANGKATAN 2019 FAKULTAS EKONOMI DAN BISNISISLAM UIN SJECH M. DJAMIL DJAMBEK BUKITTINGGI) - Muhammad Alghazali; Amsah Hendri Doni (BORJUIS: JURNAL OF ECONOMY, 2025)
This research was inspired by the extensive use of the LinkAja Syariah application by students enrolled in sharia banking courses at UIN Sjech M. Djamil Djambek Bukitinggi. This research seeks to determine and analyze the relationship between product quality and customer satisfaction using the LinkAja Syariah digital wallet. It is part of the Islamic banking program at UIN Sjech M. Djamil Djambek Bukitinggi. A quantitative technique is used in this investigation. One hundred and ten persons were surveyed for this study. At the same time, the data analysis method employs determinant coefficient (R2), simple linear regression analysis, and hypothesis testing (t test) to examine the relationship between dependent and independent variables. Research out of UIN Sjech M. Djamil Djambek Bukittinggi's sharia banking course reveals that the quality of the product significantly impacts customer satisfaction with the LinkAja Syariah digital wallet.